Anaerobic Co-Digestion of Human Feces with Rice Straw for Biogas Production: A Case Study in Sunyani. (15th September 2022) - Adjama, Irédon; Derkyi, Nana Sarfo Agyemang; Uba, Felix; Akolgo, Gilbert Ayine; Opuko, Richard
Abstract : The choice of feedstock for biogas production should not only be limited to organic waste like agricultural products, food, and animal waste. Human feces could also be considered a source of biogas production. The ever-increasing cost of fossil fuels and environmental pollution threats are forcing the search for alternative energy sources. Several types of research have to unlock the mysteries behind the difficulties of producing biogas from human feces, especially the production of more HN3, which is a greenhouse gas because of its low C:N ratio. This research experimentally investigated how to reduce their amount using rice straw with a high C:N ratio. Several combinations were made between the human waste and the rice straw at different ratios during the experiment. The result shows that the optimal outcome for methane production fell on the 50% HF and 50% RS combination due to the actions of both aerobic and anaerobic processes.